A Validated HPLC Method for Quantitation of Rosmarinic Acid in a Polyherbal Syrup - Sara Zakerin; Homa Hajimehdipoor; Seyed Alireza Mortazavi*; Rasool Choopani; Shirin Fahimi; Masoumeh Sabetkasaei; Fatemeh Tavakolifar (Iranian Society of Pharmacognosy, 2020)
Herbal medicines play a significant role in global healthcare systems. In this investigation, "Monzej soda" syrup was prepared by decocting a mixture containing Lavandula angustifolia, Melissa officinalis, Echium amoenum, Cordia myxa, Glycyrrhiza glabra, Ziziphus jujuba, Foeniculum vulgare, Fumaria parviflora, Adiantum capillus-veneris and Alhagi spp. Manna. along with glycerin, sodium benzoate and potacium sorbate. Physicochemical characteristics of the syrup were examined. Moreover, an HPLC technique was designed for analysis of rosmarinic acid in the syrup using C18 column, isocratic H3PO4 0.085% as the mobile phase, flow rate of 1 ml/min in λmax 330 nm. The method was validated for selectivity, linearity, precision, accuracy, LOD and LOQ. The herbal syrup was brown color with special taste and flavor. Density, pH, viscosity, dry residue, total phenolics, rosmarinic acid content were found 1.085 g/ml, 5.56, 5.35 cP, 15.22±0.43 %, 194 mg/100ml and 47.5 mg/100 ml, respectively. The syrup was stable during laboratory stability tests. The HPLC method was valid according to selectivity, linearity (72-110 µg/ml, r2: 0.9995), intra-day and inter-day precisions (RSD%˂2), accuracy (103.38-106.47%), LOD 1.6 µg/ml and LOQ 4.9 µg/ml. The syrup is a good candidate for pharmaceutical companies after pharmacological and clinical tests.